Nanostructured Molecularly Imprinted Photonic Polymers for Sensing Applications - Latif, Usman; Mujahid, Adnan; Zahid, Muhammad; Mustafa, Ghulam; Hayat, Akhtar (Current Nanoscience, 2020)
This review article focused on fabrication of sensors by using a combination of highly ordered photonic crystals and molecular imprinted polymers as artificial recognition materials. In this article, we have discussed fundamental principle of photonic crystals, various synthetic approaches and their use in sensing applications. Moreover, nanostructuring of recognition materials, by using photonic crystals, for sensor fabrication and sensing mechanism has also been discussed. Molecular imprinted photonic polymer layers have been applied for developing sensor devices for diverse analytes such as environmental toxins, nerve gas agents, explosives, drug molecules and others. A comprehensive comparison of molecular imprinted photonic polymers based sensor systems has also been summarized in the table which contains all the related information about colloidal structure, polymer system including monomer, cross-linker and initiator as well as target analytes. Finally, emerging strategies and current challenges involved in the design of more efficient molecular imprinted photonic sensors and their possible solutions are also briefly discussed.
Keywords: sensors